IMPACT OF AI TOOLS ON ACADEMIC WRITING AND THEIR INFLUENCE ON CRITICAL THINKING AND WRITING SKILLS AMONG MALAYSIAN UNIVERSITY LECTURERS - Mazlan, Nur Dania; Rahim, Norsafinar (Journal of Engineering and Technology (JET), 2025)
Artificial intelligence (AI) tools like Grammarly and ChatGPT are increasingly used in higher education, transforming academic writing and teaching practices. This study explores how Artificial Intelligence (AI) tools impact academic writing, critical thinking, and professional development among Malaysian university lecturers. By utilising a qualitative approach, data were gathered from ten lecturers through open-ended surveys and have been analysed using Braun and Clarke’s six-step thematic analysis. Findings show that while these AI tools improve writing efficiency, grammar, and idea development, it also raises concerns about over-reliance, reduced critical engagement, and ethical issues like citation inaccuracy and plagiarism. Some lecturers valued AI for supporting brainstorming and reflection, while other lecturers felt it limited analytical depth. In teaching, AI tools were used for planning and assessments but remained supplementary. The study highlights the need for human oversight to ensure academic integrity and critical thinking. It recommends implementing ethical guidelines, promoting AI literacy, and supporting professional development to guide responsible AI integration. These findings provide timely insights into how Malaysian lecturers navigate the benefits and challenges of Artificial Intelligence (AI) tools in academic writing and pedagogy.